Oxymoron in English and Arabic Modern Poetry: A Contrastive linguistic Study - Al-Mawla, Fida'; Falih, Besmaa Majid (International Journal of Psychosocial Rehabilitation, 2020)
The present study is a contrastive linguistic study of using of oxymoron as a linguistic device in English and Arabic languages and particularly in poetry. It is mainly concerned with investigating the term ’oxymoron’ in both languages by examining its definitions, types, uses or reasons, structures, meanings and the terms included within this term in both languages. Likewise, the study investigates and shows the similarities and differences between English and Arab modern poets in using oxymoron as a figure of speech in their poems. For these purposes, it is hypothesized that: (1) oxymoron, in all its types, is used in both English and Arabic modern poetry (2) English and Arab poets frequently employ oxymorons in their poems to convey particular meanings, and (3) oxymoron in English and Arabic is similar and/or different in certain cases, like terminology and which type preferred. To achieve the purposes and to prove the hypotheses, a qualitative analysis of two poems in both languages is made to verify the results. The model used to analyze the chosen data is a designed eclectic one derived mainly from Leech’s model (1969) ’’A linguistic Guide to English Poetry’’ and Shen’s model (1987) ’’On the Structure and Understanding of Poetic Oxymoron’’, in addition to other sources taken from Arab and English authors, like Ofuani (1990), Flayih (2009), Sloane (2001) and Abu-Jaber (2013). The study ends with the results verifying what has already been proposed by the researcher in terms of matching the results with the hypotheses established and the objectives desired in the study.